The Effect of Moringa Climbing Plant (Moringa oleifera Lamk) on Growth Herbal Chili (Piper retrofractum Vahl) at Bluto Sumenep Madura - Catur Wasonowati; Mustika Tripatmasari; Moh. Dwi Zainol Akbar (Nusantara Science and Technology Proceedings, 2022)
The herbal chili plant (Piper retrodractum Vahl) is one of the potential medicinal plants in Indonesia. This plant includes plants that have climbing roots on their trunk segments so that they require climbing poles for growth. The purpose of this study was to determine the effect of Moringa climbing poles on the growth of herbal chili plants in Bluto Sumenep Madura. This research was carried out in the chili herb garden owned by farmers in Bluto District in September 2022. This research was conducted by survey using an exploratory descriptive method on the land of chili herbal farmers using climbing Moringa plants in Bluto District. Sampling was done by using purposive sampling method. Sumenep Regency is a center for herbal chili plants, one of which is in Bluto District. The herbal chili plants in Bluto are widely cultivated using climbing poles of Moringa plants. Moringa plants are propagated by cuttings because they are used for climbing poles for herbal chilies. The climbing pole of Moringa was chosen because of its long life, the roots of the herbal chili pepper can be attached and grow well, easy to grow, resistant to pruning and do not have a detrimental effect on the growth of the herbal chili plant.